2021
DOI: 10.3390/molecules26030733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Culture Supernatant on Cariogenic Biofilm Formation and RANKL-Induced Osteoclastogenesis in RAW 264.7 Macrophages

Abstract: Postbiotics are a promising functional ingredient that can overcome the limitations of viability and storage stability that challenge the production of probiotics. To evaluate the effects of postbiotics on oral health, eight spent culture supernatants (SCSs) of probiotics were prepared, and the effects of SCSs on Streptococcus mutans-induced cariogenic biofilm formation and the receptor activator of the nuclear factor κB ligand (RANKL)-induced osteoclastogenesis were evaluated in RAW 264.7 macrophages. SCS of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…Both NF-κB and MAPK pathways are triggered by a common group of PRRs, and thus, the downstream events may be affected simultaneously, leading to the attenuated inflammatory response through decreased NF-κB activity and MAPK phosphorylation. This has been observed for HKB and CSF and also isolated postbiotic factors such as 8.7 kDa proteins from L. plantarum 10hk2 CFS [96], L. rhamnosus LGG-derived DNA [97], HKB of Weissella cibaria JW15 [98], and CFS of L. salivarius MG4265 [99]. In all of these studies, the decreased NF-κB activity (inhibition of IκBα degradation and/or translocation) and p38 phosphorylation were observed.…”
Section: Postbiotics' Influence On Nf-κb and Mapk Pathwayssupporting
confidence: 58%
“…Both NF-κB and MAPK pathways are triggered by a common group of PRRs, and thus, the downstream events may be affected simultaneously, leading to the attenuated inflammatory response through decreased NF-κB activity and MAPK phosphorylation. This has been observed for HKB and CSF and also isolated postbiotic factors such as 8.7 kDa proteins from L. plantarum 10hk2 CFS [96], L. rhamnosus LGG-derived DNA [97], HKB of Weissella cibaria JW15 [98], and CFS of L. salivarius MG4265 [99]. In all of these studies, the decreased NF-κB activity (inhibition of IκBα degradation and/or translocation) and p38 phosphorylation were observed.…”
Section: Postbiotics' Influence On Nf-κb and Mapk Pathwayssupporting
confidence: 58%
“…Previous studies have shown that Lactobacillus reuteri could more effectively alleviate patients’ symptoms, improve the microbial environment around the implant, and exert a better therapeutic effect on PI 28 . The study of Jae-In Jung showed that Lactobacillus plantarum has great potential as a multifunctional oral health ingredient that inhibits biofilm formation and suppresses the alveolar bone loss associated with periodontitis 29 . However, the relevant studies have not indicated the substances and mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Lactobacillus reuteri could more effectively alleviate patients' symptoms, improve the microbial environment around the implant, and exert a better therapeutic effect on PI 21 . The study of Jae-In Jung showed that Lactobacillus plantarum has great potential as a multifunctional oral health ingredient that inhibits bio lm formation and suppresses the alveolar bone loss associated with periodontitis 22 . However, the relevant studies have not indicated the substances and mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%